Contemporary Visual Arts in Africa in the Age of Regeneration and Transformation - Onipede, Akinwale (NIU Journal of Humanities; Vol 10 No 1 (2025): NIU Journal of Humanities, Vol. 10 No. 1, March 2025DO - 10.58709/niujhu.v10i1.2111, 2025)
This study aims at examining contemporary visual arts of Africa vis-à-vis the tendencies of renewal and hybridization of concepts, perspectives and creative energies on the continent. Contemporary visual arts of Africa have been making headway into global prominence through a number of avenues which include exhibitions, critical discourses, auctions and publications, so much unlike in the past when only the traditional arts enjoyed such visibility. Initially, modern/contemporary visual arts of Africa were derided, with aspersions cast on the authenticity of works produced after contact with the West. The notion that modern/contemporary African arts had dissolved into artistic practices and philosophy of the West and consequently, no longer authentic but an appendage, appears to have given way to the realization that artistic practices all over the world are not static or impermeably exclusive. That it is expected that contemporary visual arts anywhere is receptive and dynamic, capable of being reinvented and influenced by practices locally and elsewhere due to interconnectivity of cultures occasioned by globalization. The recent new expressions in contemporary African arts therefore attest to the rebirth and repackaging of the traditional models and viewpoints on the continent. Contemporary visual arts in Africa comprise of a vast range of practices and products out of which notable ones and their artists are studied. Data are obtained through library research, interview and observation and are presented through verbal and pictorial descriptions. Keywords and Phrases: contemporary visual arts of Africa, renewal, hybridization, global prominence, globalization.